Pengembangan Media Pembelajaran Audio Visual dengan Model Discovery Learning pada Pembelajaran PPKn untuk Meningkatkan Nilai-Nilai Persatuan Indonesia di Kelas IV Sekolah Dasar - Fitriani, Melvi; Widi Winarni, Endang; Juarsa, Osa (Jurnal Kajian Pendidikan Dasar, 2025)
The aim of carrying out this development research is to develop learning media audio visual with models discovery learning on PPKn learning to improve the values of Indonesian unity in grade IV elementary school. The research was conducted at SDN 75 Bengkulu City in class IV. This research is Reseach and Development (R&D) with the ADDIE model with stages Analysis (analysis), Design (design), Development (development), Implentation (implementation), and Evaluation (evaluation). The instruments used were feasibility test questionnaires and student response questionnaires and teacher interview guidelines. The feasibility test was carried out by 6 validators, namely 2 material experts, 2 language experts and 2 presentation experts. User response testing was carried out on 30 class IV students and 1 class teacher in the experimental class. The results of the learning media feasibility test were carried out by validators in terms of material, language and design aspects, material feasibility was obtained at 0.88 (high criteria), language feasibility results were 0.93 (high criteria) and design feasibility results were 0.94 (high criteria). The results of the learning media field test by conducting posttests and pretests with the gain test results showing 3 students with a high criterion gain count, 16 students with medium criteria, then 5 students with low criteria, then 5 students with no decline criteria and the criteria for a decline 1 student. Apart from that, the results of interviews with class IV teachers showed a positive response. Based on the results obtained, it can be concluded that learning media is suitable for use.